The Use of Online Spelling Bee Game in Teaching Vocabulary - Amelia, Andi Resky; Farahdiba, Syarifah; G, Hasriani (Program Studi Pendidikan Bahasa Inggris FBS UNM, 2024)
This study is arranged to know the effect of the use of spelling bee online game to students’ vocabulary mastery in English subject. This thesis has a problem statement namely, does the Spelling Bee Online Game give effect on students’ vocabulary, and the objective of this research is to find out the effect of spelling bee online game on students’ vocabulary. This research used the pre-experimental method which is the part of quantitative method . while, the population of this research is seventh grade student of SMPN 3 MARBO and the sample of this research was 25 students from class VII A. The instrument of this research was vocabulary text. The research used a spelling bee online game, with the pretest used to determine the students' basic vocabulary competence and the posttest used to determine the students' vocabulary improvement following the treatment. There were twenty items on the test, with five options for each number. Next, SPSS 22 was used to compute and analyze the test. The study concludes that spelling bee online game is useful for increasing seventh-grade students’ vocabulary at SMPN 3 Marbo. A notable difference in the students’ mean scores on the pretest and posttest served as evidence. The pretest mean score was 31.60, whereas the posttest score was 76.60, and the value of the sig (2-tailed) was 0.000.